Smart planning & smart cities. - Exner, Jan-Philipp (My University, 2014)
In the light of a comprehensive social and technological change, spatial planning is confronted with major changes in its basic conditions. It is faced with an increasing ubiquity of spatial relevant information of which the potentials and risks need to be discussed in the use for planning purposes. Besides the increasing pervasion of sensors in everyday life and the use of mobile communication devices, the networking and communication possibilities will play a major role in the conception of a connected and "smart" city. In addition to the above mentioned aspects and social networking capabilities, it seems that committed citizens appear increasingly as active stakeholders for planning purposes via inductive processes. Based on the mentioned technological possibilities, topics such as Smart Cities are increasingly being discussed in the public debate in recent times. It is unclear if the term "Smart City" is based more on a scientific foundation or on marketing ideas. And what can planners do, to make the city smarter and especially to make it a better place for people to live? This paper embraces an examination of the various technologies and methodological approaches in relation to planning-relevant information and knowledge creation. Besides the proclaimed potential of making a city more efficient, there will also be a critical consideration of the problems of having a city, where all urban data is connected.
Keywords: Stadtplanung; Stadtentwicklung; Technologieeinsatz; Informationstechnologie; Kommunikationstechnologie; Datenerfassung; Smart City; Stadtmanagement; Steuerung; Top Down-Verfahren; Bottom-up-Prinzip; Planungsansatz; Vernetzung